Appraising The Evidence for Conservative versus Surgical Management of Motor Deficits in Degenerative Cervical Radiculopathy. Issue 2 (March 2023) - Gebreyohanes, Axumawi; Erotocritou, Marios; Choi, David
Study Design: Systematic review. Objectives: Understanding the prevalence and outcome of motor deficits in degenerative cervical radiculopathy is important to guide management. We compared motor radiculopathy outcomes after conservative and surgical management, a particular focus being painful vs painless radiculopathy. Methods: MEDLINE and EMBASE databases were searched. We stratified each study cohort into 1 of 6 groups, I–VI, based on whether radiculopathy was painful, painless or unspecified, and whether interventions were surgical or non-surgical. Results: Of 10 514 initial studies, 44 matched the selection criteria. Whilst 42 (95.5%) provided baseline motor radiculopathy data, only 22 (50.0%) provided follow-up motor outcomes. Mean baseline prevalence of motor deficits was 39.1% (9.2%–73.3%) in conservative cohorts and 60.5% (18.5%–94.1%) in surgical cohorts. Group VI, 'surgically-managed motor radiculopathy with unclear pain status' had the largest number of cohorts. Conversely, no cohorts were found in Group III, 'conservatively-managed painless motor radiculopathy'. Large disparities in data quality made direct comparison of conservative vs operative management difficult. Conclusions: Overall pre-intervention prevalence of motor deficits in degenerative cervical radiculopathy is 56.4%. Many studies fail to report motor outcomes after intervention, meaning statistical evidence to guide optimal management of motor radiculopathy is currently lacking. Our study highlights the need for more evidence, preferably from a prospective long-term study, to allow direct comparisons of motor outcomes after conservative and surgical management.